2023
DOI: 10.3390/bios13080833
|View full text |Cite
|
Sign up to set email alerts
|

Insole Systems for Disease Diagnosis and Rehabilitation: A Review

Zhiyuan Zhang,
Yanning Dai,
Zhenyu Xu
et al.

Abstract: Some chronic diseases, including Parkinson’s disease (PD), diabetic foot, flat foot, stroke, elderly falling, and knee osteoarthritis (KOA), are related to orthopedic organs, nerves, and muscles. The interaction of these three parts will generate a comprehensive result: gait. Furthermore, the lesions in these regions can produce abnormal gait features. Therefore, monitoring the gait features can assist medical professionals in the diagnosis and analysis of these diseases. Nowadays, various insole systems based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…Kour et al (2022) and Bosel et al (2020), as explored within this review, have utilized simple 2-D video camera apparatus to gather biomechanical data, indicating possible areas for future inquiry [32,30]. Recent exploration of inertial sensor-based methods presents a more clinically applicable approach, in which wearable sensor technology is used to track and measure patient biomechanical data outside of a laboratory setting [14]. However, this alternative often comes at the expense of quality and the number of features able to be collected [52].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kour et al (2022) and Bosel et al (2020), as explored within this review, have utilized simple 2-D video camera apparatus to gather biomechanical data, indicating possible areas for future inquiry [32,30]. Recent exploration of inertial sensor-based methods presents a more clinically applicable approach, in which wearable sensor technology is used to track and measure patient biomechanical data outside of a laboratory setting [14]. However, this alternative often comes at the expense of quality and the number of features able to be collected [52].…”
Section: Discussionmentioning
confidence: 97%
“…Existing studies have shown that alterations in the temporospatial and biomechanical parameters have been positively correlated to increasing severity of KOA [13]. While traditional approaches towards gait analysis utilize motion capture and cameras to capture parameters, often with high accuracy in laboratory settings, contemporary advancements in wearable sensor technology have facilitated a remote, cost-effective, and accessible method, often at the cost of accuracy and depth of information [14]. The ability for biomechanical data to be applied towards the diagnosis and prognosis prediction for KOA can increase accessibility for patients, and allow for earlier access to treatment, possibly relegating KOA to a preventable disease in the future [15].…”
Section: Introductionmentioning
confidence: 99%